Understanding Psychological Wellbeing Among Iranian Healthcare Workers: The Role of Resilience and Social Capital - Maryam Akbari; Mohammad Hossein Kaveh; Rosanna Cousins; Hamidreza Mokarami; Mehdi Jahangiri; Changiz Rahimi Taghanaki (Journal of Health Sciences and Surveillance System, 2025)
Background: Psychological well-being is a protective factor against mental disorders. This study aimed to clarify the contribution of resilience and social capital as predictors of psychological well-being as a first step toward developing evidence-based interventions to improve psychological wellbeing in healthcare workers.Methods: This cross-sectional study was conducted on Iranian healthcare workers. Systematic random sampling was used to recruit 140 employees working in healthcare centers in Shiraz, Iran, in 2021. Data were collected using a survey that included Ryff’s Scale of Psychological Well-Being, the Social Capital at Work Scale, and the Resilience at Work Scale. Data analysis involved correlations and path analysis to clarify the relationship between predictor variables for psychological well-being in healthcare workers.Results: Significant relationships were found between psychological well-being and resilience (r=0.29, P<0.01), psychological wellbeing and social capital (r=0.31, P<0.01), and resilience and social capital (r=0.42, P<0.01). Path analysis revealed a significant and direct relationship between social capital and resilience (β=0.56, P=0.001) as well as resilience and psychological well-being (β=0.59, P=0.001). The direct path from social capital to psychological wellbeing was insignificant (β=0.00, P=0.93). The model explained 36% of the variance in psychological well-being.Conclusion: Resilience was the most influential predictor of psychological well-being. It was associated with psychological well-being both directly and indirectly through the contribution of social capital. Promoting individual empowerment and developing resilience skills should be considered an essential approach in designing and implementing intervention programs to improve the psychological well-being of healthcare workers.